Developing Syariah Tourism in Aceh: Potencies and Challenges - Heriani, Heriani; Baiquni, M; Wijono, Djoko; Widyaningsih, Yulia A. (E-Journal of Tourism; Volume 5 Number 2 (September 2018)DO - 10.24922/eot.v5i2.42717, 2018)
Syariah Tourism is growing rapidly due to the high expenditure of the global Muslim market for the tourism sector which leads to the lifestyle and the typical needs of Muslims to be a very important thing to be presented in every tourism service. Aceh as one of the provinces in Indonesia which is known by the implementation of Sharia’ is one of the priority areas of  Syariah Tourism development. However, what and how the halal tourism is is not widely known yet, so that some potencies and resources of halal tourism in Aceh, especially Banda Aceh has not been well developed. This study aims to determine the public perception about Syariah tourism as well as to know what are the potencies and challenges in the development of  Syariah Tourism in Aceh. This research uses the qualitative method with interview and observation. The results show that Syariah tourism is not only understood as a great opportunity for Aceh tourism, but it is also an obligation in Islam and the culture of Acehnese, so it must be implemented in every tourism development in Aceh. Potencies of Syariah Tourism in Aceh is the cultural values of society that is based on Islamic values, Aceh Islamic heritage with religiosity atmosphere, and then tsunami heritage that presents spiritual value to tourists. However, these potencies are also challenging because the belief and stigma that Aceh is majority of Islam, so that all things are 100% halal, so as in terms of hygiene, and service at tourist attractions are still needserious attention Keywords: Syariah Tourism, Aceh, Perception , Potencies, Challenges